Contextual Learning with Toy Money Media to Improve the Understanding of The Money Concept of Students with Mild Mental Disabilities - Relingga, Devi Rintan; Frasida, Sofa Amalia; Ruby , Arcivid Chorynia (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aims to analyze the effectiveness of contextual learning assisted by play money media in improving the understanding of the concept of money in students with mild mental retardation. The background of the problem stems from the low ability of children with mental retardation in recognizing and using money, which hinders their independence in everyday life. The main question of this study is: How can the application of contextual learning with play money media improve the understanding of the concept of money in students with mental retardation? The novelty of this study lies in the integration of contextual learning and the use of concrete media in the form of play money in a simulation of buying and selling activities, which has not been studied in depth before. Research Methods: The method used is descriptive qualitative research with a case study design on one student with mild mental retardation in class 3C at SLB Negeri Kaliwungu, through participatory observation, interviews, and documentation. Finding/Results: The results of the study showed that this approach was effective in improving students' understanding of the form, value, and function of money, as well as training social skills and independence in the context of simple transactions. Conclusion: This study concludes that contextual learning with play money media provides a real, fun, and relevant learning experience to the lives of students with mental retardation, and has the potential to be used as a life skills learning model in SLB.